Killer-Cell Inhibitory Receptors, CD158a/b, are Upregulated by Interleukin-2, but not Interferon-γ or Interleukin-4. Issue 6 (1999) - Kogure, Toshiaki; Fujinaga, Hiroshi; Niizawa, Atsushi; Hai, Le Xuan; Shimada, Yutaka; Ochiai, Hiroshi; Terasawa, Katsutoshi
Abstract : Although it is now accepted that killer-cell inhibitory receptors (KIRs), which were molecularly cloned in 1995, deliver negative signals to natural killer (NK) cells regarding the recognition of target cells, it is still unclear how the expression of these receptors on lymphocytes is regulated. Therefore, we investigated the regulation of expression of representative KIRs, CD158a and CD158b, by cytokines such as interleukin-2 (IL-2), IL-4 and interferon-γ (IFN-γ). Neither IL-4 nor IFN-γ affected the expression of CD158a/b, but incubation for 48 h with IL-2, which enhances the killer activity of NK cells, upregulated the expression of the KIRs. This upregulation by IL-2 was also observed in CD16-positive cells sorted from total lymphocytes. In contrast, IL-4, which is a downregulator of IL-2-induced killer responses, did not change the level of CD158a/b expression when added after the IL-2 treatment. These findings suggest that IL-2 plays an important role in the regulation of CD158a/b expression, and might be involved in controlling NK activity via regulating expression of these molecules.